Pattern reversal visual evoked potentials in the interictal and postictal periods in cases with epileptic seizures and non-epileptic psychogenic seizures - Berilgen, M. S.; Surgun, F.; Mungen, B.; Bulut, S. (Wiley-Blackwell, 2010)
[Abstract Not Available]
14th Congress of European-Federation-of-Neurological-Societies -- SEP, 2010 -- Geneva, SWITZERLAND